The actually online banking consumer - Carlos Martínez-de-Ibarreta; Aurora Ruiz-Rua; Covadonga Gijón; Fernando Fernández-Bonilla (International Telecommunications Society (ITS), 2024)
This paper carries out an exhaustive analysis of the implementation of e-banking in Spain, the impact of the reduction of bank branches and how both phenomena affect the elderly and the rural world. This allows us to take a picture of the user affected by the digital divide when using e-banking and to get to know them to support them in the digitisation process. The study is conducted by developing a logit model with random effects and a complete descriptive study of the panel data from the survey on equipment and use of information and communication technologies in households between 2017 and 2021, obtaining very important results: the fewer bank branches per thousand inhabitants, the greater the propensity to use e-banking, age and the development of e-skills are a differentiating factor in the adoption of e-banking services, a strong gender gap remains, there is no deep implementation of the other tools provided by digital banking. It is necessary to enhance the financial and online knowledge of individuals to maximise their usefulness in the use of digital banking services.
Keywords: 330; traditional banking; online banking; consumers; survey data; econometric models